Public Perceptions of Powdered Alcohol Use and Misuse: Narrative Perspectives from YouTube. Issue 4 (4th July 2018) - Barry, Adam E.; Muraleetharan, Daenuka; Nelon, Jordan; Lautner, Shelby; Callahan, Megan; Zhang, Xiaoying; Herren, Michelle; Chaney, Beth; Stellefson, Michael
ABSTRACT: Background : Powdered alcohol, a new form of crystalline alcohol sold under the brand name Palcohol, has yet to be widely distributed in the United States due to political and public concerns surrounding potential for misuse.Purpose : Given the limited research on powdered alcohol, researchers examined YouTube videos on this controversial substance to gain insights into its use.Methods : Researchers thematically evaluated YouTube videos describing knowledge of powdered alcohol use, its effects, as well as the cultural context surrounding its use.Results : Of the videos that met study inclusion criteria ( n  = 210), 38% were coded as "news report, " 20% "opinion, " 19% "policy, " 11% "user-generated information, " 7% "education, " 3% "misuse, " 2% "development, " and 1% "use." One in three videos about powdered alcohol included negative viewpoints about the product ( n  = 71, 34%).Discussion : The majority of reviewed YouTube videos described negative implications of consuming powdered alcohol (eg, high potential for unintentional over consumption).Translation to Health Education Practice : Findings suggest ways in which health researchers can use popular social media websites, such as YouTube, to address divides between sensationalized public perceptions of chronic health risks and evidence-based research of new alcoholic products.